Burn this night : a novel - Kenna, Alex (Crooked Lane, 2024)
"Struggling private investigator Kate Myles is shattered to learn her late father isn't her biological dad. She's still reeling when she discovers that an unknown distant relative is the prime suspect in a decades-old murder investigation. Trying to convince her to take on the case for free, an old colleague recommends her as an investigator for a recent arson murder in the same small town. After giving up on a failed acting career, Abby Coburn is starting over as a promising social work student. With her life on the right track, she's determined to help her brother, Jacob, whose meth addiction triggered a psychotic break and descent into crime. But when Abby dies in a fire that kills two other people and destroys part of the town, the police immediately suspect Jacob. As the Coburn family grapples with the tragedy, Kate begins unraveling the cold case but finds herself caught in the middle of an emotional minefield. Pretty soon, she discovers that this town is full of dark secrets, and as she comes closer and closer to figuring out the truth, Kate must solve both murders before she becomes the next victim"--